Investigating the roles of polyamines in the predator-prey interactions of Bdellovibrio bacteriovorus. - Ford, Rhian Marie (2025)
This project examines the life and behaviour of the predatory bacterium B. bacteriovorus HD100, focusing on how polyamine systems in either the predator or its prey may affect predatory dynamics. This thesis was inspired by the original work of Varon and colleagues in 1983, revisiting their observation that exogenous polyamines rescued the delayed completion of predation seen in diluted cultures of a Bdellovibrio-like predator mixed with prey Photobacterium leiognathi. To examine this phenomenon, this work examined the largely unknown role of polyamines in B. bacteriovorus by investigating potential polyamine transport systems, proposing a polyamine biosynthesis pathway and collaboratively testing potential polyamine-sensing chemotaxis receptor proteins. In the first results chapter, a putative active ABC putrescine/spermidine importer and a putative putrescine exporter were examined by gene deletion in B. bacteriovorus HD100. Collaborative HPLC analysis of intracellular polyamine content of these mutants compared to Wild Type showed changes in polyamine concentrations. These changes were suggestive of the predicted import and export roles. Neither putative polyamine transport mutant abolished intracellular levels of polyamines suggesting the presence of other transport systems or an intact biosynthetic polyamines pathway. Fluorescently tagging the periplasmic binding protein of the ABC transport system showed that the periplasmic protein required the membrane protein components for localisation or expression. In the second results chapter, the three predicted stages within polyamine biosynthesis in B. bacteriovorus HD100 were studied, expected to result in the production of putrescine and spermidine. The biosynthetic pathways were investigated by attempting to generate gene deletions for three enzymes responsible for each step. Deletion of a predicted arginine decarboxylase, the highest enzyme in the biosynthetic pathway, was not tolerable, suggesting conversion of arginine into agmatine is essential in B. bacteriovorus when cultured with E. coli prey. Deletions of the genes predicted to encode an agmatinase and a putative fusion protein S-adenosylmethionine decarboxylase/spermidine synthase, were successfully generated with predatory growth still seen. Deletion of the putative agmatinase, potentially blocking all polyamine biosynthesis, delayed the rate of predatory cycle completion with exogenous polyamines unable to rescue this delay. No effect was seen when deleting the putative fusion enzyme which catalyses the subsequent step in the biosynthetic pathway converting putrescine to spermidine. This indicated a potentially less important role for spermidine biosynthesis or putrescine conversion. In the final results chapter, attempts were made to provide biological relevance to putative polyamine and propionate chemotactic receptors in a collaborative project. These preliminary experiments demonstrate the considerations required when attempting to assay motility and chemotaxis in B. bacteriovorus with an evaluation of the methodologies tested. Preliminary turn angle data indicated a kinetic response of Wild Type B. bacteriovorus to propionate. This research shows that complex systems were likely at play in Varon’s initial experiments regarding polyamines and predation. Alterations to predatory dynamics may be impacted by polyamine biosynthesis, transport or through responses to polyamines, possibly through chemotactic behaviour or regulation of gene expression. Further investigation is required however to determine the exact roles of polyamines throughout each stage of the B. bacteriovorus predatory lifestyle.